Reusing equipment in cells reconfiguration for a lean and sustainable production - Dias, Mariana (2019)
Production cells are considered a flexible production system capable to face new market demands. In most cases, this is provided by their capability of reconfiguration, i.e., by removing/adding new equipment needed and/or reusing the existent equipment for the new demand. Nevertheless, some companies are not conveniently exploring this opportunity. What happened, many times, is the design of a complete new cell replacing all the equipment and sending the existent machinery to the warehouse. This is a decision that, economically and environmentally, is costly. Furthermore, knowing that some equipment could be reused for a new product. In a Lean Thinking, this is waste and a Lean company should promote a more efficient and sustainable production. This paper introduces a study in a Lean company that has developed practices to reuse equipment. The reasons for the non-reuse of the existent equipment were studied and some strategies were proposed to turn this equipment available and visible for reuse. Also, the benefits of reusing equipment related with saved costs and contribution to the environmental sustainability, are discussed.